The effect of high and low frequency noise on anxiety and sleep disorder in male rats - Gharibreza Nazerirad; Fatemeh Zare Mehrjerdi; Fatemeh Khojasteh (Mashhad University of Medical Sciences, 2021)
Abstract Background and Aim: Environmental noise pollution can cause physical and mental disorders, especially in cities. This study aimed to investigate the effects of Low-Frequency (LF) and High-Frequency (HF) noise on anxiety and sleep disorder in male rats. Materials and Methods: Fifteen male Wistar rats were randomly divided into three groups: 1) control group (no exposure to noise), 2) group exposed to low-frequency traffic noise (LF group), and 3) group exposed to high-frequency traffic noise (HF group). Sleep duration was monitored by CCTV. Anxiety-like behaviors were measured using the Elevated Plus Maze (EPM). Results: The results of the EPM test showed that time spent in the open arm was significantly lower in the HF group than in the control (P <0.05). Sleep duration was significantly lower in rats exposed to LF and HF noise (P <0.01). There was no significant difference in sleep duration between the HF and LF groups. Conclusion: Exposure to high and low-frequency noise can reduce sleep duration and high-frequency noise can increase anxiety-like behavior in rats.